Ilmu Nahwu dan Pengaruhnya Terhadap Istinbat Hukum Fikih - Sam, Zulfiah; Saadal Jannah; Wahyuni Ishak (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2021)
This research aimed to examine the metters surrounding the science of Nahwu in the form of understanding, the law of studying it and its virtue as seen from its position in syarâ€™i science and its effect on the istinbaá¹ of fiqh laws. The method used in this research was library research. The result of this study indicated that the sciences of Nahwu has major influence on the istinbath of laws related to fiqh issues, such as the differences between Syafiâ€™iyah and Malikiyah on the problem of mandatory head sweeping when ablution, differences in Jumhur Ulama on the problem of how to purify the feet when performing ablution, whether to wash them. Or it is enough just to wipe it, as well as the differnces between Syafiâ€™iyah and Hanafiyah in the problem of the fetus that was slaughtered by its mother.